2021
DOI: 10.4149/neo_2021_210113n57
|View full text |Cite
|
Sign up to set email alerts
|

Homoharringtonine inhibits the progression of hepatocellular carcinoma by suppressing the PI3K/AKT/GSK3β/Slug signaling pathway

Abstract: Homoharringtonine (HHT), was first isolated from the bark of Cephalotaxus harringtonia (Knight ex J. Forbes) K. Koch and Cephalotaxus fortunei Hook trees. The bark extract is used to treat leukemia and in recent years has also been used in traditional Chinese medicine (TCM) to treat solid tumors. However, the inhibitory mechanism of HHT in the progression of hepatocellular carcinoma (HCC) is rarely studied. We aimed to evaluate the antitumor efficacy of HHT on HCC in vitro and in vivo and elucidate the underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…However, the detailed targets by which HHT activated PI3K/AKT/mTOR signaling remain for further investigation. Consistent with our findings, HHT suppressed cell proliferation, migration, invasion, EMT and facilitated apoptosis in hepatocellular carcinoma via inhibiting PI3K/AKT/GSK3β/Slug signaling [ 41 ]. PI3K/AKT inhibitor LY294002 potentiated the anti-myeloma activity of HHT both in vitro and in vivo [ 42 ].…”
Section: Discussionsupporting
confidence: 89%
“…However, the detailed targets by which HHT activated PI3K/AKT/mTOR signaling remain for further investigation. Consistent with our findings, HHT suppressed cell proliferation, migration, invasion, EMT and facilitated apoptosis in hepatocellular carcinoma via inhibiting PI3K/AKT/GSK3β/Slug signaling [ 41 ]. PI3K/AKT inhibitor LY294002 potentiated the anti-myeloma activity of HHT both in vitro and in vivo [ 42 ].…”
Section: Discussionsupporting
confidence: 89%
“…This was consistent with previous studies reporting that the PI3K/AKT signaling pathway participates in the inhibiting activity of HHT in colorectal cancer 40 and hepatocellular carcinoma. 42 TIMP1 interacts with other proteins to cause aberrant regulation of downstream signaling pathways, among which the PI3K/AKT pathway is one of the main TIMP1-related signaling pathways. 19 In colon cancer, TIMP1 promotes cell proliferation and metastasis by activating the FAK/PI3K/AKT pathway, and selective FAK or AKT inhibitors impair the pro-tumor effects of TIMP1.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 It has also recently been used for the traditional Chinese medicine treatment of solid tumours. Moreover, HHT can suppress tumour cell growth in melanoma, 6 myeloma, 7 lymphoma, 8 liver cancer, 9 pancreatic cancer, 10 and lung cancer, 11,12 exerting a broad anti-tumour effect. Wang et al showed by miRNA sequencing that HHT inhibits growth and promotes apoptosis of human breast cancer cells through the miR-18a-3p/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) signalling pathway.…”
mentioning
confidence: 99%